Neurodevelopmental Outcomes of Infants with Benign Enlargement of the Subarachnoid Space - Nasiri, Jafar; Madihi, Yahya; Mirzadeh, Azadeh Sadat; Mohammadzadeh, Mahdi (Iranian Journal of Child Neurology, 2021)
Objective Benign enlargement of the subarachnoid space (BESS) is the most common cause of macrocephaly in infants. This study aimed to evaluate the neurodevelopmental outcomes in infants with BESS. Materials & Methods In this follow-up study, all records of infants diagnosed with BESS in 2012-2016 were assessed. A clinical follow-up examination was carried out at 6, 12, 18, and 24 months of age to assess the macrocephaly outcomes. Denver Developmental Screening Test-II (DDST-II) was used for evaluating the psychomotor development of infants at 24 months of age. All data were entered in SPSS Version 13, and descriptive statistics were measured. Results Out of 32 infants included in this study, 28 (87.5%) were boys. Five cases of prematurity history (15.6%), and 23 cases of macrocephaly in the family (71.9%) were recorded. The mean age of BESS diagnosis was 6.8 months (SD=3.2). subdural hematoma was reported in one infant (3.1%). Also, 28 infants showed macrocephaly at 18 months of age (83.3%). Seven patients had developmental delay, according to DDST-II (22%). The mean head circumference at birth and six months of age was significantly greater in infants with developmental delay compared to those with normal development. There was a significant difference between the mean head circumference at birth (P=0.05) and the mean head circumference at six months of age (P=0.02). Conclusion Developmental delay is frequent in BESS infants, especially those with macrocephaly at birth and six months of age, and requires medical attention